2008
DOI: 10.1038/sj.mp.4002131
|View full text |Cite
|
Sign up to set email alerts
|

Activin tunes GABAergic neurotransmission and modulates anxiety-like behavior

Abstract: Activin, a member of the transforming growth factor-b superfamily, affords neuroprotection in acute brain injury, but its physiological functions in normal adult brain are largely unknown. Using transgenic (tg) mice expressing a dominant-negative activin receptor mutant under the control of the CaMKIIa promoter in forebrain neurons, we identified activin as a key regulator of c-aminobutyric acid (GABA)ergic synapses and anxiety-like behavior. In the open field, wildtype (wt) and tg mice did not differ in spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 56 publications
6
58
0
1
Order By: Relevance
“…Moreover, theta oscillation (35) and the hippocampal GABAergic system play a prominent role in certain forms of emotional processing, with special emphasis on anxiety-like behavior (23)(24)(25). The present study showed that CAPS2-KO mice exhibited not only decreased frequency of hippocampal theta oscillations but also increased anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Moreover, theta oscillation (35) and the hippocampal GABAergic system play a prominent role in certain forms of emotional processing, with special emphasis on anxiety-like behavior (23)(24)(25). The present study showed that CAPS2-KO mice exhibited not only decreased frequency of hippocampal theta oscillations but also increased anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 49%
“…S6). Impaired hippocampal GABA neurotransmission and decreased BDNF levels are thought to affect hippocampus-related learning and anxiety-like behavior (23)(24)(25). Interestingly, CAPS2-KO mice displayed increased anxiety-like behavior (Table S1) but showed little impairment in learning and memory tests.…”
Section: Morphological Abnormalities In Gabaergic Interneuron Systems Inmentioning
confidence: 99%
“…There is also evidence that TGF-␤ signaling contributes to neurodegeneration in Alzheimer's disease (Tesseur et al, 2006;Ueberham et al, 2006) and altered cognitive abilities (Loeys et al, 2005). In addition, it has been found that components of TGF-␤ signaling pathway are altered in the hippocampus in human psychiatric conditions such as schizophrenia and bipolar disorder (Benes et al, 2007), and manipulation of TGF-␤ signaling has been proposed as a possible treatment for anxiety and depression (Dow et al, 2005;Ageta et al, 2008;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-␤ signaling also regulates synaptic transmission and plasticity in multiple circuits in different organisms including glutamergic transmission at the Drosophila neural muscular junction (McCabe et al, 2004), cholinergic transmission between motoneurons and interneurons in the CNS of Drosophila (Baines, 2004), glutamergic transmission between sensory and motor neurons in Aplysia ganglia (Zhang et al, 1997), and modulation of hippocampal network in mammals (Fukushima et al, 2007;Sun et al, 2007;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Signalling through the canonical pathway is involved in multiple aspects of neurodevelopment, adult neurogenesis and neuroprotection (reviewed in 33). There is evidence that TGF signalling contributes to neurodegeneration in Alzheimer's disease (34,35) and influences cognitive abilities and the level of cognitive decline between male and female schizophrenia patients (36,37); further, it is altered in the hippocampus in schizophrenia and bipolar disorder (38) and in anxiety and depression (39)(40)(41).…”
Section: Tgf-β In Schizophreniamentioning
confidence: 99%